2005
DOI: 10.1007/s10526-004-5279-y
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits of the acarophagous lady beetle,Stethorus japonicus at three constant temperatures

Abstract: Stethorus japonicus Kamiya (Coleoptera: Coccinellidae) is an indigenous ladybird beetle in Japan, which feeds on many spider mite species. We evaluated the development, survivorship and life-history parameters of this lady beetle on a diet of eggs of the two-spotted spider mite, Tetranychus urticae Koch (red form) (Acari: Tetranychidae). In addition, the effect of short photoperiod on its reproduction was assessed. Survival rates from egg to adult were more than 71% at temperatures between 17.5 and 30°C. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…Each adult female may consume 30-60 mites per day. Total fecundity ranges from 123 eggs in S. tridens (Fiaboe et al, 2007), 184 eggs in S. madecassus (Chazeau, 1974a, b), 221 in S. punctum (Tanigoshi and McMurtry, 1977), 279 in S. punctillum (Roy et al, 2003), to a high of 501 eggs in S. japonicus (Mori et al, 2005 2002; Tanigoshi and McMurtry, 1977). The number of Stethorini generations per year varies from 2 to 3 in temperate regions for S. punctillum and S. punctum (Putman, 1955a;Colburn and Asquith, 1971) to more than 15 per year for tropical species such as S. siphonulus and S. pauperculus (Puttaswamy and Rangaswamy, 1976;Puttaswamy and ChannaBasavanna 1977).…”
Section: Developmental and Prey Consumption Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each adult female may consume 30-60 mites per day. Total fecundity ranges from 123 eggs in S. tridens (Fiaboe et al, 2007), 184 eggs in S. madecassus (Chazeau, 1974a, b), 221 in S. punctum (Tanigoshi and McMurtry, 1977), 279 in S. punctillum (Roy et al, 2003), to a high of 501 eggs in S. japonicus (Mori et al, 2005 2002; Tanigoshi and McMurtry, 1977). The number of Stethorini generations per year varies from 2 to 3 in temperate regions for S. punctillum and S. punctum (Putman, 1955a;Colburn and Asquith, 1971) to more than 15 per year for tropical species such as S. siphonulus and S. pauperculus (Puttaswamy and Rangaswamy, 1976;Puttaswamy and ChannaBasavanna 1977).…”
Section: Developmental and Prey Consumption Ratesmentioning
confidence: 99%
“…Since the developmental times differ little among species of Stethorini, the differences in r m -values between species are attributable to differences in reproductive rates (Mori et al, 2005) (Table 2). At 24-25°C the r m -values for Stethorus species range from 0.100 in S. punctillum (Roy et al, 2003) to 0.160 in S. loi (Shih et al, 1991); a number of other species have been evaluated and found to fall within this range (Chazeau, 1974a,b;Fiaboe et al, 2007;Mori et al, 2005;Richardson, 1977;Tanigoshi and McMurtry, 1977). Sabelis (1985aSabelis ( ,b, 1991 calculates that the r m -values for tetranychid mites range from 0.160 to 0.293 at around 25°C.…”
Section: Developmental and Prey Consumption Ratesmentioning
confidence: 99%
“…In particular, the response of St. japonicus in this study conflicted with this supposition: St. japonicus was rare on the shoots on which A. viennensis or T. urticae were introduced. St. japonicus is well-known as an extremely voracious predator (Gotoh et al, 2004;Mori et al, 2005). Thus, the numbers of A. viennensis and T. urticae were so small in this experiment that St. japonicus may have not responded to these spider mites.…”
Section: Discussionmentioning
confidence: 80%
“…Three predacious insects native to Japan, Stethorus japonicus H. Kamiya (Coleoptera: Coccinellidae), Oligota kashmirica benefica Naomi (Coleoptera: Staphylinidae), and Scolothrips takahashii Priesner (Thysanoptera: Thripidae), are prospective natural enemies of spider mites because of their voracity and reproductive capacity (Shimoda et al, 1993;Kishimoto, 2003;Gotoh et al, 2004a, b;Mori et al, 2005;Kishimoto and Adachi, 2008). As these species are specialized predators of spider mites, their occurrences on plants usually synchronize with those of spider mites (Takahashi et al, 2001;Kishimoto, 2002;Gotoh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%